Magnetic Hyperthermia and Oxidative Damage to DNA of Human Hepatocarcinoma Cells - Cellai, Filippo (Int J Mol Sci, 2017)
Nanotechnology is addressing major urgent needs for cancer treatment. We conducted a study to compare the frequency of 3-(2-deoxy-β-d-erythro-pentafuranosyl)pyrimido[1,2-α]purin-10(3H)-one deoxyguanosine (M(1)dG) and 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG) adducts, biomarkers of oxidative stress and/or lipid peroxidation, on human hepatocarcinoma HepG2 cells exposed to increasing levels of Fe(3)O(4)-nanoparticles (NPs) versus untreated cells at different lengths of incubations, and in the presence of increasing exposures to an alternating magnetic field (AMF) of 186 kHz using (32)P-postlabeling. The levels of oxidative damage tended to increase significantly after ≥24 h of incubations compared to controls. The oxidative DNA damage tended to reach a steady-state after treatment with 60 μg/mL of Fe(3)O(4)-NPs. Significant dose–response relationships were observed. A greater adduct production was observed after magnetic hyperthermia, with the highest amounts of oxidative lesions after 40 min exposure to AMF. The effects of magnetic hyperthermia were significantly increased with exposure and incubation times. Most important, the levels of oxidative lesions in AMF exposed NP treated cells were up to 20-fold greater relative to those observed in nonexposed NP treated cells. Generation of oxidative lesions may be a mechanism by which magnetic hyperthermia induces cancer cell death.